Penerapan Model Pembelajaran Inkuiri terhadap Hasil Belajar Siswa pada Mata Pelajaran Geografi - Fernandi Seni Banari; Hermon Maurits Karwur; Irfan Rifani (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2023)
The purpose of this study was to determine how the application of the inquiry learning model to student learning outcomes in Geography subjects at SMA Negeri 5 Halmahera Utara. Non-randomized control group pretest and posttest design were used in the research method, which is a quasi-experimental approach. The findings show the strong influence of the inquiry learning model on student learning outcomes for lithosphere material in the subject of Geography. This shows that the results of the posttest data analysis test using a t-test with a significance threshold of 0.05, where tcount > ttable is 14.91 > 1.76, is significant. Based on observations, the application of the inquiry learning model in the experimental class compared to conventional learning, its application was at a very good level of 93%.